Kitaibel Pálnak, a királyi magyar tudományegyetem professzorának tanulmányai - Both, Mária (Gerundium, 2016)
The Studies of Pál Kitaibel, Professor of the Hungarian Royal University. During the Age of Enlightenment the field of natural sciences went through fundamental changes that are present until this day. One of the most famous natural philosophers of the age in Europe was Hungarian Pál Kitaibel, who created the still valid basis for the description of the flora, natural geography and landscape research of the Carpathian Basin. Little is known about his student years at the Royal Academy of Győr (1777–78) and at theMedical Faculty of the Royal Hungarian Science University (1780–84), which provided him with a wide range of knowledge in natural sciences. With the help of historical documents pertaining to the age this study investigates the approximately ten years of Kitaibel’s life from a culture-historical and pedagogical point of view in connection with the evolving Hungarian natural scientific thinking.